(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Fayalite (Fe2SiO4) as the main composition of copper slag contains abundant Fe2+. Reasonable application of fayalite is of great interest for comprehensive use of mineral resource and reduction of environmental problems. In this work, the oxidation behavior of fayalite in water vapor was investigated. Fayalite was decomposed into magnetite (58.8 wt%), hematite (21.6 wt%) and silica (19.6 wt%) at 1000 °C for 40 min under water vapor condition. Compared with the result obtained in dry air, water vapor could promote fayalite to transform into magnetite by decreasing oxygen fugacity. In addition, the iron oxide product was further enriched via alkaline cleaning in 1 mol/L NaOH. As for the gas product, the hydrogen production capacity reached 24.41 mL/g when exposed to 50 vol% water-50 vol% Ar at 1000°C for 40 min.